2023
DOI: 10.1186/s13046-023-02607-2
|View full text |Cite
|
Sign up to set email alerts
|

GPX8 regulates clear cell renal cell carcinoma tumorigenesis through promoting lipogenesis by NNMT

Abstract: Background Clear cell renal cell carcinoma (ccRCC), with its hallmark phenotype of high cytosolic lipid content, is considered a metabolic cancer. Despite the implication of this lipid-rich phenotype in ccRCC tumorigenesis, the roles and regulators of de novo lipid synthesis (DNL) in ccRCC remain largely unexplained. Methods Our bioinformatic screening focused on ccRCC-lipid phenotypes identified glutathione peroxidase 8 (GPX8), as a clinically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…By stimulating the Wnt signaling pathway, GPX8 is transcriptionally controlled by FOXC1 and aids in the proliferation of gastric cancer cells( 39 ). Through encouraging lipogenesis by NNMT, GPX8 controls the development of clear cell renal cell carcinoma tumors( 40 ). However, when it comes to its involvement in cancer, particularly glioblastoma, there is limited information available.…”
Section: Discussionmentioning
confidence: 99%
“…By stimulating the Wnt signaling pathway, GPX8 is transcriptionally controlled by FOXC1 and aids in the proliferation of gastric cancer cells( 39 ). Through encouraging lipogenesis by NNMT, GPX8 controls the development of clear cell renal cell carcinoma tumors( 40 ). However, when it comes to its involvement in cancer, particularly glioblastoma, there is limited information available.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a decreased GPD1 level was also found in serum samples of TNBC patients, suggesting the possible use of GPD1 as a diagnostic biomarker 135 . In kidney cancer, overexpression of GPD1 downregulated various lipid synthesis genes, leading to a decrease in lipid droplets 17 , the enrichment of which is a characteristic and cancer-requiring feature of ccRCC 136 138 . In addition to these lipid metabolic changes, decreased cell proliferation, migration, and invasion, as well as the inhibition of xenografted tumor growth, were also observed, consistent with the correlation between high GPD1 protein levels and better ccRCC patient survival.…”
Section: Glycerol Phosphate Dehydrogenases In Cancermentioning
confidence: 99%
“…Notably, due to enhanced differential expression between RCC subtypes and healthy tissue detected through several techniques such as immunohistochemistry, ELISA and proteomic analysis, NNMT has been proposed as a biomarker for the diagnosis of the main RCC subtypes, in combination with other markers [ 166 , 167 , 168 ]. Furthermore, several in vitro studies reported that NNMT downregulation was associated with a decreased proliferation and invasiveness in ccRCC cells [ 166 , 169 , 170 , 171 , 172 ]. In the light of these observations, the enzyme seems to be a promising diagnostic and prognostic biomarker, which could be also utilized as a therapeutic target due to the large number of NNMT inhibitors available and currently tested for cancer treatment [ 173 , 174 , 175 , 176 , 177 , 178 ].…”
Section: Novel Strategiesmentioning
confidence: 99%